Experimental investigation of esophageal reconstruction with electrospun polyurethane nanofiber and 3D printing polycaprolactone scaffolds using a rat model. Issue 3 (26th November 2020) - Park, Hanaro; Kim, In Gul; Wu, Yanru; Cho, Hana; Shin, Jung‐Woog; Park, Su A; Chung, Eun‐Jae
Abstract: Background: We evaluated the outcome of esophageal reconstructions using tissue‐engineered scaffolds. Method: Partial esophageal defects were reconstructed with the following scaffolds; animals were grouped (n = 7 per group) as follows: (a) normal rats; (b) rats implanted with three‐dimensional printing (3DP) polycaprolactone (PCL) scaffolds; (c) with human adipose‐derived mesenchymal stem cell (ADSC)‐seeded 3DP PCL scaffolds; (d) with polyurethane (PU)‐nanofiber(Nf) scaffolds; and (e) with ADSC‐seeded PU‐Nf scaffolds. Results: The esophageal defects were successfully repaired; however, muscle regeneration was greater in the 3DP PCL + ADSC groups than in the PU‐Nf + ADSC groups ( P < .001). Regeneration of the epithelium was greater in PU‐Nf and PU‐Nf + ADSC groups than in the 3DP PCL and 3DP PCL + ADSC groups ( P < .001). Conclusion: A tendency for more re‐epithelization was observed with the PU‐Nf scaffolds, while more muscle regeneration was achieved with the 3DP PCL scaffolds.